Reimagining History Education: A Critical Exploration of Transforming University Historical Laboratories into Educational Tourism Destinations - Andy Suryadi; Ganda Febri Kurniawan; Putri Agus Wijayati; R Soeharso; Nurul Asyikin Binti Hassan; Andriyanto Andriyanto; Junaidy Fery Lusianto (Paramita: Historical Studies Journal, 2025)
Abstract: This study explores the potential of university-based historical laboratories as educational tours, offering an alternative pathway for history learning. Employing a qualitative case study methodology, the research used interviews, observations, and focus group discussions to collect data, which was analyzed through an interactive data analysis model. Findings underscore the robust potential of university historical laboratories as viable educational tours. Key indicators include well-equipped facilities, proficient human resources, and substantial institutional support, forming a strong foundation for future development. These laboratories enrich educational experiences and serve as dynamic platforms for fostering deeper historical understanding among students. The study advocates for the expansion and refinement of historical education tours centered around the concept of university historical laboratories. This approach emphasizes integrating educational principles with historical exploration, enhancing engagement and learning outcomes. By leveraging existing academic resources and infrastructures, universities can effectively revitalize history education, aligning educational practices with contemporary pedagogical needs. In conclusion, this research highlights the transformative potential of historical laboratories within university settings, advocating for their strategic integration into educational tourism initiatives. Moving forward, it is imperative to cultivate these initiatives with a deliberate focus on educational quality and historical authenticity, ensuring that they serve as dynamic tools for enriching historical education both locally and globally. Abstrak: Penelitian ini mengeksplorasi potensi laboratorium sejarah di perguruan tinggi sebagai bentuk wisata edukatif, menawarkan jalur alternatif dalam pembelajaran sejarah. Dengan menggunakan metode studi kasus kualitatif, data dikumpulkan melalui wawancara, observasi, dan diskusi kelompok terfokus (FGD), lalu dianalisis menggunakan model analisis data interaktif. Hasil penelitian menunjukkan bahwa laboratorium sejarah di perguruan tinggi memiliki potensi kuat sebagai destinasi wisata edukatif. Indikator utamanya mencakup fasilitas yang memadai, sumber daya manusia yang kompeten, serta dukungan kelembagaan yang solid—semuanya menjadi fondasi penting untuk pengembangan lebih lanjut. Laboratorium ini tidak hanya memperkaya pengalaman belajar, tetapi juga menjadi ruang dinamis yang mendorong pemahaman sejarah yang lebih mendalam bagi siswa. Penelitian ini mendorong pengembangan wisata edukatif sejarah berbasis laboratorium sejarah kampus. Pendekatan ini mengintegrasikan prinsip pendidikan dengan eksplorasi sejarah, sehingga meningkatkan keterlibatan dan hasil belajar. Dengan memanfaatkan sumber daya akademik dan infrastruktur yang ada, perguruan tinggi dapat menghidupkan kembali pendidikan sejarah agar lebih relevan dengan kebutuhan pembelajaran masa kini. Sebagai kesimpulan, laboratorium sejarah di lingkungan kampus memiliki potensi transformatif dan layak diintegrasikan secara strategis dalam inisiatif wisata edukatif. Ke depan, pengembangan ini perlu diarahkan pada peningkatan mutu pendidikan dan keaslian sejarah, agar dapat menjadi sarana pembelajaran yang bermakna di tingkat lokal maupun global.